Acute effects of breaking up prolonged sitting on fatigue and cognition: a pilot study. Issue 2 (26th February 2016) - Wennberg, Patrik; Boraxbekk, Carl-Johan; Wheeler, Michael; Howard, Bethany; Dempsey, Paddy C; Lambert, Gavin; Eikelis, Nina; Larsen, Robyn; Sethi, Parneet; Occleston, Jessica; Hernestål-Boman, Jenny; Ellis, Kathryn A; et al.
Abstract : Objectives: To compare the acute effects of uninterrupted sitting with sitting interrupted by brief bouts of light-intensity walking on self-reported fatigue, cognition, neuroendocrine biomarkers and cardiometabolic risk markers in overweight/obese adults. Design: Randomised two-condition crossover trial. Setting: Laboratory study conducted in Melbourne, Australia. Participants: 19 overweight/obese adults (45–75 years). Interventions: After an initial 2 h period seated, participants consumed a meal-replacement beverage and completed (on 2 days separated by a 6-day washout period) each condition over the next 5 h: uninterrupted sitting (sedentary condition) or sitting with 3 min bouts of light-intensity walking every 30 min (active condition). Primary outcome measures: Self-reported fatigue, executive function and episodic memory at 0 h, 4 h and 7 h. Secondary outcome measures: Neuroendocrine biomarkers and cardiometabolic risk markers (blood collections at 0 h, 4 h and 7 h, blood pressure and heart rate measured hourly and interstitial glucose measured using a continuous glucose monitoring system). Results: During the active condition, fatigue levels were lower at 4 h (−13.32 (95% CI −23.48 to −3.16)) and at 7 h (−10.73 (95% CI −20.89 to −0.58)) compared to the sedentary condition. Heart rate was higher at 4 h (4.47 (95% CI 8.37 to 0.58)) and at 7 h (4.32 (95% CI 8.21 to 0.42)) during the active condition compared to the sedentary condition. There were no significant differences between conditions by time for other variables. In the sedentary condition, changes in fatigue scores over time correlated with a decrease in heart rate and plasma dihydroxyphenylalanine (DOPA) and an increase in plasma dihydroxyphenylglycol (DHPG). Conclusions: Interrupting prolonged sitting with light-intensity walking breaks may be an effective fatigue countermeasure acutely. Fatigue levels corresponded with the heart rate and neuroendocrine biomarker changes in uninterrupted sitting in this pilot study. Further research is needed to identify potential implications, particularly for the occupational health context. Trial registration number: ACTRN12613000137796; Results.